Structural Steel Tensile Fracture-Inception Prevention Limit State and Ductility Criteria - Adewole Kazeem Kayode; de Dieu Mutabaruka Jean (Civil and Environmental Engineering, 2020)
This paper proposes using the tensile-fracture-inception-prevention (TFIP) limit state and ductility parameter/criterion for a safer fracture-resistant design of the tension members of steel structures. Finite element (FE) analysis revealed that the tensile band localization strain (TBLS) is significantly lower than the fracture strain currently employed as the structural steel elongation-based ductility parameter/criterion. The TBLS is thus, a safer fracture-resistant parameter/criterion than the fracture strain. FE analysis reveals that the TBLS at the center of tension specimens (mid-thickness and mid-width) is lower, and is thus a safer TFIP elongation-based ductility criteria/parameter than the TBLS at the surface of tension specimens.